Gambaran Tingkat Pengetahuan Masyarakat terhadap Swamedikasi Diare di Desa Krembung Kabupaten Sidoarjo pada Bulan Maret 2020 - Patrinila Mery Chresna (AFAMEDIS, 2021)
Self-medication or self-medication is behavior to deal with minor illnesses before seeking help from an officer or health facility. More than 60% of the community members are swamed, and 80% of them rely on modern medicine. Diarrhea is defecation with liquid consistency (diarrhea) 3 times or more in one day (24 hours). The purpose of this study was to determine the description of diarrhea swamedication behavior patterns among the people of Krembung Village in Sidoarjo in 2020. This study used a purposive sampling technique in swamedication patterns for one month. The results of this study showed that patients with male gender were 47% and female patients were 53%. The description of the level of community knowledge about self-medicated diarrhea in Krembung Sidarjo village was 16 respondents (6%) had a poor level of knowledge, 190 respondents (71%) had a sufficient level of knowledge, 62 respondents (23%) had a good level of knowledge. In general, the description of the level of community knowledge about diarrhea self-medication in Krembung village, Sidoarjo district in March 2020 was 70.57% or it could be said that it was sufficient